Aerodynamical and mechanical design of turbine blade - Santos, Sônia Magalhães dos; Pinho, Jean Monteiro de; Keller, Pablo Passos; Dias, Gustavo Cunha; Santos, Elizaldo Domingues dos (VETOR - Revista de Ciências Exatas e Engenharias, 2010)
The present work presents a study concerned with the project of a wind turbine. This task is basically shared in two steps. The first one is the blades aerodynamic project, with the purpose of taking more advantage of the wind kinetic energy and the second one is concerned with the mechanical project of the blades, in order to support the loads over the blades during the operation period. The graphical modeling and the mechanical project of the blades are performed with the computational softwares AutoCad® and Excel. The commercial code Ansys® is employed to analyze the mechanical resistance and the reliability of the blade. To perform the prediction of the wind action efforts over the blade is used the aerodynamic analysis including forces, such as: axial, tangential, weight and centrifugal ones, and aerodynamic momentum. The blades are composed of fiberglass shell reinforced with plastic material. Vertical and horizontal reinforcements of wood and carbon fiber, respectively, are also employed.